Is Estrogen a Missing Culprit in Thyroid Eye Disease? Sex Steroid Hormone Homeostasis Is Key to Other Fibrogenic Autoimmune Diseases – Why Not This One? - FitzPatrick, Amy M. (Frontiers in Immunology, 2022)
Sex bias in autoimmune disease (AID) prevalence is known, but the role of estrogen in disease progression is more complex. Estrogen can even be protective in some AIDs; but in systemic lupus erythematosus (SLE), rheumatoid arthritis (RA), and systemic sclerosis (SSc), estrogen, its metabolites, and its receptors have been demonstrated to play critical, localized inflammatory roles. Estrogen is instrumental to the fibrosis seen in RA, SLE, SSc and other disease states, including breast cancer and uterine leiomyomas. Fibrotic diseases tend to share a common pattern in which lymphocyte–monocyte interactions generate cytokines which stimulate the deposition of fibrogenic connective tissue. RA, SLE, SSc and thyroid eye disease (TED) have very similar inflammatory and fibrotic patterns—from pathways to tissue type. The thorough investigations that demonstrated estrogen’s role in the pathology of RA, SLE, and SSc could, and possibly should, be carried out in TED. One might even expect to find an even greater role for estrogen, and sex steroid homeostasis in TED, given that TED is typically sequalae to Graves’ disease (GD), or Hashimoto’s disease (HD), and these are endocrine disorders that can create considerable sex steroid hormone dysregulation. This paper highlights the pathophysiology similarities in 4 AIDs, examines the evidence of sex steroid mediated pathology across 3 AIDs and offers a case study and speculation on how this may be germane to TED.